Influence of mental health medication on microbiota in the elderly population in the Valencian region - Pesantes, Nicole; Barberá, Ana; Pérez-Rocher, Benjamí; Artacho, Alejandro; Vargas, Sergio Luís; Moya, Andrés; Ruiz-Ruiz, Susana (Frontiers in Microbiology, 2023)
Spain has an aging population; 19.93% of the Spanish population is over 65. Aging is accompanied by several health issues, including mental health disorders and changes in the gut microbiota. The gut-brain axis is a bidirectional network linking the central nervous system with gastrointestinal tract functions, and therefore the gut microbiota can influence an individual’s mental health. Furthermore, aging-related physiological changes affect the gut microbiota, with differences in taxa and their associated metabolic functions between younger and older people. Here we took a case-control approach to study the interplay between gut microbiota and mental health of elderly people. Fecal and saliva samples from 101 healthy volunteers over 65 were collected, of which 28 (EE|MH group) reported using antidepressants or medication for anxiety or insomnia at the time of sampling. The rest of the volunteers (EE|NOMH group) were the control group. 16S rRNA gene sequencing and metagenomic sequencing were applied to determine the differences between intestinal and oral microbiota. Significant differences in genera were found, specifically eight in the gut microbiota, and five in the oral microbiota. Functional analysis of fecal samples showed differences in five orthologous genes related to tryptophan metabolism, the precursor of serotonin and melatonin, and in six categories related to serine metabolism, a precursor of tryptophan. Moreover, we found 27 metabolic pathways with significant inter-group differences, including pathways regulating longevity, the dopaminergic synapse, the serotoninergic synapse, and two amino acids.